2021
DOI: 10.3390/nano11123456
|View full text |Cite
|
Sign up to set email alerts
|

Three-Layer PdO/CuWO4/CuO System for Hydrogen Gas Sensing with Reduced Humidity Interference

Abstract: The growing hydrogen industry is stimulating an ongoing search for new materials not only for hydrogen production or storage but also for hydrogen sensing. These materials have to be sensitive to hydrogen, but additionally, their synthesis should be compatible with the microcircuit industry to enable seamless integration into various devices. In addition, the interference of air humidity remains an issue for hydrogen sensing materials. We approach these challenges using conventional reactive sputter deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…It can be found that Pd element was mainly metallic Pd 0 located at 335.3 and 340.55 eV. Additionally, there were other peaks of oxidized Pd 2+ located at 336.6 and 341.85 eV and Pd 4+ located at 338.2 and 343.45 eV [32]. This also corresponds to the XRD spectra.…”
Section: Morphology and Structuresupporting
confidence: 60%
See 1 more Smart Citation
“…It can be found that Pd element was mainly metallic Pd 0 located at 335.3 and 340.55 eV. Additionally, there were other peaks of oxidized Pd 2+ located at 336.6 and 341.85 eV and Pd 4+ located at 338.2 and 343.45 eV [32]. This also corresponds to the XRD spectra.…”
Section: Morphology and Structuresupporting
confidence: 60%
“…It can be found that Pd element was mainly metallic Pd 0 located at 335.3 an 340.55 eV. Additionally, there were other peaks of oxidized Pd 2+ located at 336.6 and 341.8 eV and Pd 4+ located at 338.2 and 343.45 eV [32]. This also corresponds to the XRD spectr A small amount of oxidized Pd came from the partial oxidation of surface atoms of P nanoparticles by air due to their high activity.…”
Section: Morphology and Structurementioning
confidence: 89%
“…The morphologies of the CuWO 4 nanocrystals in different environments, that is, under synthesis conditions, the conditions for carbon dioxide reduction, ,, and the conditions for water splitting, were determined based on the surface phase diagrams discussed in the previous sections. The Wulff morphologies were constructed using the atomic configuration with the lowest surface free energy for each surface, using the following relationships σ 1 d 1 = σ 2 d 2 = · · · = σ n d n = c , where σ and d represent the surface free energy and the distance from the center to the surface of the crystal.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The sensor exhibited a three times higher response towards n-butanol as compared to the sensitive layer composed of pristine WO 3 . Kumar [20] proposes CuWO 4 /WO 3-x films, prepared by reactive magnetron sputtering, for hydrogen sensing and proves its enhanced performance towards this gas as compared to pristine CuO and WO 3 . Finally, Wang [21] studies the role of electron transfer behavior induced by CO chemisorption on visible-light-driven CO conversion over WO 3 and CuWO 4 /WO 3 in order to explain its higher gas sensing performance.…”
Section: Introductionmentioning
confidence: 99%